Approach to Risk Management Decision-Making in the Small Business - Myšková Renáta; Doupalová Veronika (Elsevier Science BV, 2015)
The defining of long-term oriented goals and methods of achieving them is always associated with uncertainty, because we cannot assume that we know all the circumstances, either positive or negative, which might occur in the future. The management of a small business has to decide under uncertainty and insecurity, and has to take into account the risks that are associated with the business. The aim of this paper is to identify risks that could significantly affect the performance of the small enterprise and to define and analyse the risk in a particular company, including methods that should be used for risk assessment.
Přístup k řízení rizik v malém podniku
Keywords: risks; risk management; management decision; small business; riziko; řízení rizik; manažerské rozhodování; malý podnik